Understanding Genomic Knowledge in Rural Appalachia: The West Virginia Genome Community Project - Jennifer A Mallow; Laurie A Theeke; Patricia Crawford; Elizabeth Prendergast; Chuck Conner; Tony Richards; Barbara McKown; Donna Bush; Donald Reed; Meagan E. Stabler; Jianjun Zhang; Geri Dino; et al. (Rural Nurse Organization; Binghamton University, 2015)
Purpose: Rural communities have limited knowledge about genetics and genomics and are also underrepresented in genomic education initiatives. The purpose of this project was to assess genomic and epigenetic knowledge and beliefs in rural West Virginia. Sample: A total of 93 participants from three communities participated in focus groups and 68 participants completed a demographic survey. The age of the respondents ranged from 21 to 81 years. Most respondents had a household income of less than $40,000, were female and most were married, completed at least a HS/GED or some college education working either part-time or full-time. Method: A Community Based Participatory Research process with focus groups and demographic questionnaires was used. Findings: Most participants had a basic understanding of genetics and epigenetics, but not genomics. Participants reported not knowing much of their family history and that their elders did not discuss such information. If the conversations occurred, it was only during times of crisis or an illness event. Mental health and substance abuse are topics that are not discussed with family in this rural population. Conclusions: Most of the efforts surrounding genetic/genomic understanding have focused on urban populations. This project is the first of its kind in West Virginia and has begun to lay the much needed infrastructure for developing educational initiatives and extending genomic research projects into our rural Appalachian communities.  By empowering the public with education, regarding the influential role genetics, genomics, and epigenetics have on their health, we can begin to tackle the complex task of initiating behavior changes that will promote the health and well-being of individuals, families and communities. Keywords: Rural; genetics; genomics;  focus groups: Community Based Participatory Research DOI:  http://dx.doi.org/10.14574/ojrnhc.v16i1.381